The Implementation of Digital Leadership and Its Impact on Employee Performance: A Qualitative Approach in Private Companies - Riska Rahayu; Irma Nuraeni Salsabila; Nova Yuningrat; Dina Nurul Fathiya; Ayu Lestari (Politeknik Siber Cerdika Internasional, 2025)
Digital transformation has driven significant changes in leadership practices within private companies, requiring leaders to adopt adaptive and innovative digital leadership approaches. This study aims to analyze the implementation of digital leadership and to understand its influence on employee performance in private companies. The study employs a descriptive qualitative research method, with data collected through in-depth interviews, observations, and document analysis involving leaders and employees as informants. Data analysis was conducted through data reduction, data display, and thematic conclusion drawing. The findings indicate that digital leadership implementation is manifested through the utilization of information technology in organizational communication, decision-making processes, performance monitoring, and the development of a flexible and collaborative work culture. Digital leadership has a positive influence on employee performance, particularly in improving work efficiency, task quality, motivation, and work commitment. From a qualitative perspective, employees perceive digital leadership as a more open, responsive, and participative leadership style, supported by transparent and accessible digital systems. However, the study also identifies challenges such as digital competency gaps and resistance to change. Overall, this research highlights that digital leadership plays a strategic role in enhancing employee performance and supporting organizational sustainability in the digital era.